Novel superconducting joints for persistent mode magnet applications - Speller, S; Mousavi, T; Grovenor, C; Darby, W; Aksoy, C; Davies, T; Brittles, G (Cambridge University Press, 2016)
Persistent current joints are a critical component of commercial superconducting magnets.The standard jointing method widely used in the magnet industry for technological low temperature superconducting wires such as NbTi and Nb3Sn wires uses a superconducting solder (e.g. PbBi). In these joints the physical and superconducting properties of the solder materials inevitably play an important role in the overall performance of the joint. Key requirements for superconducting solders include low melting point to prevent degradation of the superconducting filaments during joining, good wettability of the superconducting filaments, suitable liquid phase viscosity, and finally adequate superconducting properties to enable sufficient supercurrent to pass through the joint under typical operating conditions (typically at 4.2K in a field of 1 T for an MRI magnet). PbBi solder satisfies all these criteria, but restrictions on the use of lead in the magnet industry are expected in the relatively near future, so new lead-free jointing techniques need to be developed. One approach is the development of superconducting lead-free solder materials. In our work, we have focussed on the In-Sn system and ternary systems involving In and Sn as two of the elements. Thermodynamic modelling has been used to produce ternary phase diagrams of potential alloy systems, and various formulations have been fabricated in order to explore how microstructure and phase chemistry influence the superconducting properties of the solders. Alternative approaches to fabricating lead-free joints, including spot welding and cold-pressing, have also been investigated. These methods have the potential advantage of achieving direct NbTi-NbTi joints with no intermediate, lower performance superconducting material. The spot welding method produced joints with the best superconducting performance, signifiantly better than the currently used PbBi solder, but the lack of reproducibility in this technique may be a problem from an industrial point of view.